Analysis of Millennial and Gen Z Interest in Using BSI Gold Credit Services as a Future Savings Investment - Rani Febrianti; Muhammad Arif; Wahyu Syarvina (Universitas Islam Negeri Sumatera Utara, 2025)
Most people use investment as a way to manage and maintain their assets so that they can grow and obtain long-term profits. Rahmawati explains that investment itself means the activity of investing capital to obtain a profit. The purpose of this study is to analyze the interest of millennials and Gen Z in using BSI gold credit services as a future savings investment. This research is qualitative research with a descriptive analysis method that focuses on primary and secondary data sources. The results show that the level of understanding of Millennials and Gen Z towards BSI Gold Credit products is still in the early stages (early awareness). This is due to low Islamic financial literacy, the complexity of products that have not been well socialized, and the lack of digital exposure that suits the characteristics of young media. The interest of Millennials and Gen Z in BSI Gold Credit products is influenced by a combination of factors, including financial literacy, ease of digital access, Islamic principles, editing flexibility, financial goals, social influence, and trust in institutions. The main obstacles faced by the younger generation in accessing BSI Gold Credit include low Islamic financial literacy, lack of promotion on social media, limited application features, doubts about the margin system, misconceptions about credit, and the perception that the process is complicated or not digital. To increase adoption, BSI needs to improve its communication, education, and digitization of its services in line with the media consumption patterns and financial behavior of Gen Z and Millennials.